1996
DOI: 10.1080/00071669608417875
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute heat stress on heat shock protein 70 messenger RNA and on heat shock protein expression in the liver of broilers

Abstract: 1. The synthesis of heat shock protein 70 (Hsp70) mRNA and the expression of Hsp70 in the liver of broiler chickens submitted to acute heat stress (35 degrees C for 5 h) was investigated. 2. Hsp70 expression was detected by SDS-PAGE and Western blot analysis using a polyclonal antiserum against Hsp70 of Blastocladiella emersonii. The specific signal of Hsp70 mRNA was analysed by Northern blot using as probe a Hsp70 cDNA of B. emersonii. 3. An increase in the amount of Hsp70 was detected from the first up to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 25 publications
5
17
0
3
Order By: Relevance
“…The results coincide with those of Gabriel et al (1996) and Dionello et al (2001). In addition, mRNA expression of chicken HSP70 was tissue dependent, which agrees with the results of Givisiez et al (2003).…”
Section: Discussionsupporting
confidence: 82%
“…The results coincide with those of Gabriel et al (1996) and Dionello et al (2001). In addition, mRNA expression of chicken HSP70 was tissue dependent, which agrees with the results of Givisiez et al (2003).…”
Section: Discussionsupporting
confidence: 82%
“…The present study found that the transcriptional levels of HSF1 and HSP70 as well as the protein expression increased in the normal muscles of the T and T/W groups. Gabriel et al (1996) found that acute heat stress induces an increase in HSP70 mRNA in broiler liver, which is similar to that of mammals. Delezie et al (2007) indicated that HSP70 mRNA increases in the liver of broilers when transported at high stocking densities.…”
Section: Discussionmentioning
confidence: 54%
“…Losses due to mortality and impaired performance of the birds were decreased in acclimated birds, and a greater heat resistance was achieved by exposing birds to cycling temperatures (May et al 1987;Davis et al 1991) or neonatal heat stress (Arjona et al 1988(Arjona et al , 1990Yahav and Hurwitz 1996). Molecular mechanisms responsible for improved thermotolerance have not been fully elucidated (Gabriel et al 1996).It is known that heat stress and other kinds of stressors (e.g., anoxia and heavy metal ions) rapidly induce the synthesis of heat shock proteins (Hsp), which, in a normal envi- …”
mentioning
confidence: 99%